Small Molecule Inhibitors of Middle East Respiratory Syndrome Coronavirus Fusion by Targeting Cavities on Heptad Repeat Trimers - Kandeel, Mahmoud (Biomol Ther (Seoul), 2020)
Middle East Respiratory Syndrome Coronavirus (MERS-CoV) is a newly emerging viral disease with fatal outcomes. However, no MERS-CoV-specific treatment is commercially available. Given the absence of previous structure-based drug discovery studies targeting MERS-CoV fusion proteins, this set of compounds is considered the first generation of MERS-CoV small molecule fusion inhibitors. After a virtual screening campaign of 1.56 million compounds followed by cell-cell fusion assay and MERS-CoV plaques inhibition assay, three new compounds were identified. Compound numbers 22, 73, and 74 showed IC(50) values of 12.6, 21.8, and 11.12 μM, respectively, and were most effective at the onset of spike-receptor interactions. The compounds exhibited safe profiles against Human embryonic kidney cells 293 at a concentration of 20 μM with no observed toxicity in Vero cells at 10 μM. The experimental results are accompanied with predicted favorable pharmacokinetic descriptors and drug-likeness parameters. In conclusion, this study provides the first generation of MERS-CoV fusion inhibitors with potencies in the low micromolar range.